Enhancing Cultural Heritage Tourism Through a Spiritual Knowledge: The Implementation of Tri Hita Karana in Taro Village Gianyar Bali - Putu Eka Wirawan; Putu Devi Rosalina (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
Spiritual knowledge has been found significant in environmental conservation, yet its role in developing tourism is under-researched. This study aims to explore the potential of spiritual knowledge and how it is being implemented in rural tourism practices. Tri Hita Karana becomes an underpinning spiritual knowledge under this study enquiry, with Taro village was the case study. Taro reflects the community’s spiritual wisdom in their destination management. Data was collected through direct interviews with 7 key informants and observations to 3 sites. Findings showed that the implementation of Tri Hita Karana was found significant in designing three temples as tourist attractions. The implementations were identified in introducing socio-cultural functions (pawongan), maintaining spiritual uniqueness (parahyangan), and sustaining sacred architecture landscape (palemahan). The present study contributes to the cultural heritage management by emphasising spiritual knowledge in designing cultural heritage attractions. The findings can practically suggest incorporating spiritual knowledge in the heritage tourism management.